2017
DOI: 10.4103/ijccm.ijccm_317_17
|View full text |Cite
|
Sign up to set email alerts
|

Meckel\'s diverticulitis masquerading as acute pancreatitis: A diagnostic dilemma

Abstract: Meckel's diverticulum is a remnant of the proximal part of the vitellointestinal duct and is the most common congenital anomaly of the gastrointestinal tract. It may either remain asymptomatic or present with myriad of clinical presentations. Gastrointestinal bleeding is the most common presentation in children whereas it is intestinal obstruction in the case of adults. We report a 9-year-old boy who presented with acute onset of periumbilical pain and nonbilious vomiting. His clinical and laboratory parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…In the literature review including the present case, bloody stool was observed in 55/74 (74.3%) of adults and 3/9 (33.3%) of children, with a significant difference ( p = 0.019) ( Table 1 ). Although it may not be sufficient to conclude that the diagnosis of inverted Meckel’s diverticulum is usually delayed in pediatric cases because of the absence of bloody stool, eight pediatric cases, excluding the present case, resulted in ileus due to intussusception, and imaging findings of intussusception were observed significantly more often in children than in adults ( p = 0.001) [ 2 , 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. On the other hand, adult cases may have significantly more anemia due to chronic intestinal hemorrhage ( p < 0.0001) ( Table 1 ), because the adult cases do not present with the acute onset of intussusception, unlike the pediatric cases.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In the literature review including the present case, bloody stool was observed in 55/74 (74.3%) of adults and 3/9 (33.3%) of children, with a significant difference ( p = 0.019) ( Table 1 ). Although it may not be sufficient to conclude that the diagnosis of inverted Meckel’s diverticulum is usually delayed in pediatric cases because of the absence of bloody stool, eight pediatric cases, excluding the present case, resulted in ileus due to intussusception, and imaging findings of intussusception were observed significantly more often in children than in adults ( p = 0.001) [ 2 , 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. On the other hand, adult cases may have significantly more anemia due to chronic intestinal hemorrhage ( p < 0.0001) ( Table 1 ), because the adult cases do not present with the acute onset of intussusception, unlike the pediatric cases.…”
Section: Discussionmentioning
confidence: 63%
“…In total, 94 related articles were retrieved. There were 29 articles for 74 adult [ 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and 9 pediatric (age < 18 years) [ 2 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] cases including the present case] that reported the course of each case in detail. These included 55 male and 28 female patients with onset ages of 2 to 78 years.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases exist in the literature of possible pancreatitis within EP. One case has been reported of a 9-year-old in India with abdominal pain who underwent a bowel resection for a Meckel’s diverticulitis that contained inflamed ectopic pancreatic tissue [ 7 ]. Another case from the Netherlands reports a 58-year-old who presented with abdominal pain and was found to have EP within the jejunal mesentery [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Em crianças a manifestação mais comum é a hemorragia digestiva 2 . Recentemente, foi publicado um estudo retrospectivo pela Universidade de Medicina de Wenzhou na China envolvendo pacientes pediátricos de até 14 anos.…”
Section: Discussionunclassified